LATAR SOSIAL EKONOMI PERIODE MEKAH DALAM AL-QURAN - Suhada (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
The socio-economic background of the Mecca period in the Qur'an influenced the attitudes, thoughts, and souls of Arab society at that time. The function of property as a basis for horizontal action is applied in various ways and purposes. This article concludes that worldly-oriented wealth can cause people's minds and souls to lose their minds and morals. Excessive attitude towards wealth accompanied by worries of poverty can affect the attitude of ignoring other people and even God. The Qur'an describes the previous people who were destroyed in their morals because the function of property was not used properly. Assets can be used for macroeconomic management in solving crises and for the benefit of community welfare in the Mecca period.